Health and the double burden of full-time work and informal care provision—Evidence from administrative data - Schmitz, Hendrik; Stroka, Magdalena A (Labour Economics)

Two-Phase Interleaving Configuration of the LLC Resonant Converter - Analysis and Experimental Evaluation - Figge, Heiko; Grote, Tobias; Fröhleke, Norbert; Böcker, Joachim; Schafmeister, Frank (Proc. IEEE Annual Industrial Electronics Society Conference (IECON))

Integrated Magnetic for DCM-PSFB Converter - Njiende, Hugues; Li, Rongyuan; Schafmeister, Frank; Ide, Peter

Resonant capacitor clamping circuit in resonant converter - Figge, Heiko; Schafmeister, Frank

Hybrid Energy Storage System (HES) - Stille, Karl Stephan Christian; Romaus, Christoph; Böcker, Joachim (Design Methodology for Intelligent Technical Systems)

Design of a high performance ferrite magnet-assisted synchronous reluctance motor for an electric vehicle - Paradkar, Milind; Böcker, Joachim (IECON 2012 - 38th Annual Conference on IEEE Industrial Electronics Society)

Fast online model predictive control of IPMSM using parallel computing on FPGA - Leuer, Michael; Böcker, Joachim (2013 International Electric Machines & Drives Conference)

Co-simulation of an electric traction drive - Schulte, Christoph; Böcker, Joachim (2013 International Electric Machines & Drives Conference)

Low Latency Hybrid Hardware-in-the-Loop Simulator for Railway Traction System - Tong, Laisheng; Zou, Huanqing; Sun, Meng; Böcker, Joachim (2013 IEEE Vehicle Power and Propulsion Conference (VPPC))

A Novel LC Resonant Based Partial Booster Scheme for Improved Efficiency and Reduced Cost of Transformerless Photovoltaic Inverters - Krishna, D.V.M.M.; Preckwinkel, H.; Fröhleke, N.; Böcker, Joachim (PCIM Europe Conference, Nürnberg, Germany)

Verlustmodellierung und Effizienzoptimierung einer hart schaltenden, netzfreundlichen Pulsgleichrichterstufe (PFC) - Bolte, S.; Baurichter, J.; Henkenius, C.; Fröhleke, N.; Böcker, Joachim; Figge, H. (Internationaler ETG Kongress, Berlin, Germany)

Minimierung niederfrequenter Oberschwingungen in Pulsmustern für 2-Level Umrichter in Antriebssystemen mittels winkelmodulierter Partikel Schwarm Optimierung - Peter, K.; Böcker, Joachim (Internationaler ETG Kongress, Berlin, Germany)

Formaler Regelungsentwurf für netzfreundliche PFC-Ladegleichrichter unter Anwendung eines Netzbeobachters - Keuck, Lukas; Fröhleke, N.; Böcker, Joachim (Internationaler ETG Kongress, Berlin, Germany)

High efficiency photovoltaic power conditioning system - Sharabash, H.; Krishna, D.V.M.M.; Fröhleke, N.; Böcker, Joachim (PCIM Europe Conference, Nürnberg, Germany)

Can oversampling improve the dynamics of PWM controls? - Böcker, Joachim; Buchholz, O. (2013 IEEE International Conference on Industrial Technology (ICIT))

Comparison of Thyristor-Rectifier with Hybrid Filter and Chopper-Rectifier for High-Power, High-Current Application - Solanki, J.; Krishna, D.V.M.M.; Fröhleke, N.; Wallmeier, P. (PCIM Europe Conference, Nürnberg, Germany)

Dynamical modeling for series-parallel resonant converter under optimized modulation - Cao, Zhiyu; Tao, Junbing; Fröhleke, Norbert; Böcker, Joachim (2013 Twenty-Eighth Annual IEEE Applied Power Electronics Conference and Exposition (APEC))

A simplified mathematical model for DC-balancing and capacitor ripple reduction in 3-level inverters - Krishna, D. V. M. M.; Fröhleke, N.; Böcker, Joachim; Preckwinkel, H. (2013 IEEE International Conference on Industrial Technology (ICIT))

A novel low cost solar central inverters topology with 99.2% efficiency - Preckwinkel, Heiko; Bünte, Andreas; Böcker, Joachim; Fröhleke, Norbert; Dora, Krishna (2013 15th European Conference on Power Electronics and Applications (EPE))

A modular multilevel converter based high-power high-current power supply - Solanki, J.; Fröhleke, N.; Böcker, Joachim; Wallmeier, P. (2013 IEEE International Conference on Industrial Technology (ICIT))

A novel space vector modulation strategy for thyristor matrix converters - Lönneker, Michael; Böcker, Joachim (2013 15th European Conference on Power Electronics and Applications (EPE))

Logik und Metaphysik bei Adolf Trendelenburg - Peckhaus, Volker (La question de la logique dans l’Idealisme allemand. Actes du colloque de Bruxelles, 7–9 avril 2011)
Rezension: Math. Rev. MR3643861 (R. Vilkko)

MExiCo: A Library for Managing Multimodal Data Collections - Menke, Peter; Cimiano, Philipp (Procedia - Social and Behavioral Sciences)

A mesoscopic model for deep drawing of carbon fibre prepregs at large strains - Hankeln, Frederik; Mahnken, R. (Composite Structures)

Ansprache - Peckhaus, Volker (Ehrenpromotion der Fakultät für Kulturwissenschaften der Universität Paderborn an Herta Müller. Paderborn, 29.10.2012. Dokumentation)

Selbstoptimierende Betriebsstrategien für ein hybrides Energiespeichersystem aus Batterien und Doppelschichtkondensatoren - Romaus, C.

Betriebs- und Regelstrategien für den autonomen Fahrbetrieb von Schienenfahrzeugen mit Linearmotor - Henke, C.

Anreizsysteme – Eine Möglichkeit zur Verbesserung der universitären Lehre? - Kiefer, Björn; Niederhaus, Constanze; Balzani, Daniel; Bobisch, Christian A.; Gerharz, Eva; Kruggel-Emden, Harald; Schwarz, Alexander; Thielbörger, Pierre; Weiss, Gregor N. F. (Journal Hochschuldidaktik (24, 1-2))

Mehrsprachigkeit und Deutsch als Zweitsprache in der Lehrerbildung für die beruflichen Schulen. Ein Modulkonzept und dessen kritische Reflexion - Niederhaus, Constanze (Beruf – Bildung – Migration. Beiträge zur Qualifizierung des Beruflichen Bildungspersonals aus der Perspektive Migration)

Zur ausbildungsvorbereitenden Förderung der Lesekompetenz in der Sekundarstufe I - Niederhaus, Constanze (Ausbildungsvorbereitung im Deutschunterricht der Sekundarstufe I. Die sprachlich-kommunikativen Facetten von „Ausbildungsfähigkeit“)

„Die Schüler verstehen es nicht und wenn sie es nicht verstehen, dann nutzt auch die fachliche Richtigkeit nix.“ Zum Einsatz und zur Nutzung von Fachtexten und Fachkundebüchern in mehrsprachigen Lernergruppen der beruflichen Bildung - die Perspektive der Lehrerinnen und Lehrer - Niederhaus, Constanze (Info DaF (40, 6))

DaZ macht Schule! Ein Blended-Learning-Szenario für die Lehrerausbildung im Bereich Deutsch als Zweitsprache - Niederhaus, Constanze; Schäfer, Andrea (Hamburger eLearning-Magazin (10))

Sprachförderung im Fachunterricht an beruflichen Schulen - Günther, Katrin; Laxczkowiak, Jana; Niederhaus, Constanze; Wittwer, Franziska

Konzept und prototypische Umsetzung eines kollaborativen UML-Klassendiagramm-Editors für Multi-Touch-Tische - Gehle, Andreas; Quapp, Alexei

van Dalen, Dirk, "L.E.J. Brouwer. Topologist, intuitionist, philosopher. How mathematics is rooted in life [updated revision of the two volume biography ‘Mystic, geometer, and intuitionist. The life of L.E.J. Brouwer’ published 1999 and 2005]", Springer: Berlin 2013 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Edmund Husserl, "Introduction to Logic and Theory of Knowledge. Lectures 1906/07", translated by Clair Otiz Hill, Springer: Dordrecht 2008 (Edmund Husserl, Collected Works, Bd. XIII) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Friederich, Simon, “Motivating Wittgenstein’s Perspective on Mathematical Sentences as Norms”, Philosophia Mathematica (3) 19 (2011), 1–19 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Purkert, Walter, “The Double Life of Felix Hausdorff/Paul Mongré”, In: The Mathematical Intelligencer 30, No. 4, 36–50 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Sieg, Wilfried, "Hilbert’s Programs and Beyond", Oxford University Press: Oxford 2013 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Sprachvariation, Diglossie und Sprachenkonflikte im Diskurs: Zur linguistische Erforschung der Galizischen Mehrsprachigkeit in der 2. Hälfte des 19. Jahrhunderts - Ptashnyk, Stefaniya (Kulturgrenzen in postimperialen Räumen)

Stadtsprachen historisch betrachtet: Zur Beschreibung der Mehrsprachigkeit in Lemberg 1848-1900 - Ptashnyk, Stefaniya (Stadtsprache(n) - Variation und Wandel)

Rice, Adrian, “Vindicating Leibniz in the Calculus Priority Dispute: the Role of Augustus De Morgan”, in: The History of the History of Mathematics, hg. v. Benjamin Wardhaugh, Peter Lang: Oxford 2012, 89–114 - Peckhaus, Volker (Mathematical Reviews)

Brueckler, Franka Miriam/Stilinović, “Teaching Arithmetic in the Habsburg Empire at the End of the 18th Century – A Textbook Example,” In: Historia Mathematica 40 (2013), 309–323 - Peckhaus, Volker (Mathematical Reviews)

Arthur, Richard T.W., “Leibniz’s Syncategorematic Infinitesimals,” In: Archive for the History of Exact Sciences 67 (2013), Nr. 5, 553–593 - Peckhaus, Volker (Mathematical Reviews)

Dutilh Novaes, "Catarina, Formal Languages in Logic. A Philosophical and Cognitive Analysis", Cambridge University Press: Cambridge 2012 - Peckhaus, Volker (Mathematical Reviews)

Tieszen, Richard, "After Gödel. Platonism and Rationalism in Mathematics and Logic", Oxford University Press: Oxford 2011 - Peckhaus, Volker (Mathematical Reviews)

Uckelman, Sara L., “Arthur Prior and Medieval Logic”, In: Synthese 188 (2012), 349–366 - Peckhaus, Volker (Mathematical Reviews)

Sebastian Vehlken. Zootechnologien. Eine Mediengeschichte der Schwarmforschung, 2012 - Tönsing, Johanna (Tierstudien 04 (2013))

Meier, Simon: Gesprächsideale. Normative Gesprächsreflexion im 20. Jahrhundert - Ptashnyk, Stefaniya (GERMANISTIK, Heft 1-2, 2014)

Analytic evaluation of the electronic self-energy in the GW approximation for two electrons on a sphere - Schindlmayr, Arno (Physical Review B)
The GW approximation for the electronic self-energy is an important tool for the quantitative prediction of excited states in solids, but its mathematical exploration is hampered by the fact that it must, in general, be evaluated numerically even for very simple systems. In this paper I describe a nontrivial model consisting of two electrons on the surface of a sphere, interacting with the normal long-range Coulomb potential, and show that the GW self-energy, in the absence of self-consistency, can in fact be derived completely analytically in this case. The resulting expression is subsequently used to analyze the convergence of the energy gap between the highest occupied and the lowest unoccupied quasiparticle orbital with respect to the total number of states included in the spectral summations. The asymptotic formula for the truncation error obtained in this way, whose dominant contribution is proportional to the cutoff energy to the power −3/2, may be adapted to extrapolate energy gaps in other systems.